APPLICATION OF THE CASE-BASED CONCEPT MAP METHOD TO ENHANCE CRITICAL THINKING AND CLINICAL REASONING SKILLS IN NURSE PROFESSIONAL STUDENTS - Hikmi Muharromah Pratiwi; Desiyani Nani; Saryono Saryono (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2025)
Introduction: Critical thinking and clinical reasoning are essential competencies in delivering safe and effective nursing care. However, identifying effective learning strategies to foster these skills remains a challenge. This study aimed to examine the effectiveness of a case-based concept map method in improving critical thinking and clinical reasoning abilities among newly enrolled nurse professional students.Methods: This quasi-experimental study employed a one-group pre-test–post-test design without a control group. A total of 18 newly admitted nurse professional students were recruited using total sampling. The intervention involved developing concept maps based on clinical cases over one week. Clinical reasoning was assessed using quizzes with clinical vignettes, while critical thinking was measured using the Critical Thinking Disposition Inventory. Paired t-tests were used to evaluate the differences in scores before and after the intervention.Results: There was a significant improvement in total critical thinking scores following the intervention (t = 2.25, p = 0.038), particularly in the analytical and systematic thinking domains (t = 2.30, p = 0.023). Clinical reasoning scores also showed a marked increase post-intervention (t = 11.93, p < 0.001), with a mean difference of 9.56.Conclusion: The case-based concept map method is effective in enhancing both clinical reasoning and critical thinking skills among nurse professional students. Integrating this approach into nursing education may better prepare students for clinical practice by promoting deeper understanding and structured decision-making.